Seleksi Pendonor Serbuk Sari Sifat Kuantitas Endosperma Skor Tinggi pada Kelapa dalam Kopyor - Rahayu, Megayani Sri; Setiawan, Asep; Maskromo, Ismail; Purwito, Agus; Sudarsono, dan (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2019)
Endosperm quantity in kopyor coconut determines the quality of kopyor coconut. However, data of the best parental based on their progeny test is unavailable yet. In this study, we employed polycross approach and SSR molecular marker to estimate general combining ability of the best pollen contributor for the breeding purpose of this trait. Totally 151 kopyor coconuts were collected from the naturally open-pollinated population of kopyor Tall coconut Agom Lampung. The harvested nuts were rated for their endosperm quantity (scored 1-9). The analysis identified 31 paternal trees of the 53 progenies. The TJ-185 with the highest GCA has been considered as a promising paternal tree for development of high endosperm quantity of kopyor coconut.Keywords: combining ability, molecular marker, paternal trees, polycross, tall coconut